The Relationship Of Knowledge Level About Breast Cancer With Breast Self-Examination Behavior As An Early Detection Of Breast Cancer On Students Of The Faculty Of Medical Al- Azhar Islamic University - Dalilah Femilia; Fachrudi Hanafi; Made Agus Suanjaya; Shinta Wulandhari (Sean Institute, 2023)
Breast cancer is when breast cells grow uncontrollably due to abnormal changes in genes in cell division. In Indonesia, the number of cases of breast cancer in 2020 even reached 68.858 (16.6%). One prevention of breast cancer is a case detection through breast self-examination (BSE). This study was aimed to determine the relationship between the level of knowledge about breast cancer and the act of early breast self-examination (BSE) as an early detection of breast cancer in FK UNIZAR students. This research employed a cross-sectional study, conducted at the Medical Faculty of Al-Azhar Islamic University on December 1-7 2022. A total of 132 respondents were included as the research sample. The data obtained were analyzed using SPSS with statistical tests using the Spearman Rank method. The results of the study found that 20 people (71. 4%) had good knowledge with adequate behavior and 97 people (93.3%) had poor behavior. There were 7 people (25.0%) who had sufficient knowledge with adequate behavior and 7 people (6.7%) with less behavior. And the sample that had less knowledge with sufficient behavior was 1 person (3.6%). According to the results of analysis from the Spearman's rank correlation test, it obtained a p-value of 0.001 (p-value <0.05) and a correlation coefficient of 0.284 with a negative value. There is a relationship between knowledge of breast cancer and breast self-examination behavior on FK UNIZAR students of 2019, 2020, and 2021.